Upgrading the functional properties of reactive dyed cotton knits. Issue 9 (2nd September 2017) - Ibrahim, N. A.; Ibrahim, D. F.; Eid, B. M.; El-Zairy, W. M.; Tawfik, T. M.
Abstract: To cope with the greater demands for high quality protective clothing and to satisfy the ever-growing end-users' requirements, functional finishes of reactive dyed cotton knits were investigated in this study. Effect of bio, soft, anti-UV, water & oil repellent or anti-bacterial functional finish on some performance, functional and coloration properties of reactive dyed cotton knits was investigated. Experimental results revealed that the change in performance properties, the extent of improvement in the imparted functional properties as well as the variation in color properties after post-finishing were varied depending on type of functional finish, knit structure and kind of the bi-functional reactive dye. The functional finished cotton knits had excellent functional properties such as softness, anti-pilling tendency, UV-shielding, water/oil repellency, and antibacterial functionality, depending on type of the finish, without adversely affecting coloration properties of reactive dyed knitted fabrics. Additionally, SEM and EDX analysis of selected samples demonstrated the changes in their surface morphology as well as confirmed the existence of certain elements.